Systemic sclerosis sine scleroderma: a multicenter study of 1417 subjects - Diab, Sehriban; Dostrovsky, Nathaniel; Hudson, Marie; Tatibouet, Solène; Fritzler, Marvin J; Baron, Murray; Khalidi, Nader (Journal of rheumatology, 2014)
To describe the clinical and serological features of systemic sclerosis sine scleroderma (ssSSc) in a multicentered SSc cohort. Data from 1417 subjects in the Canadian Scleroderma Research Group registry were extracted to identify subjects with ssSSc, defined as SSc diagnosed by an expert rheumatologist, but without any sclerodactyly or skin involvement prior to baseline study visit or during followup. Clinical and serological features of ssSSc subjects were compared to limited (lcSSc) and diffuse cutaneous SSc (dcSSc) subjects. At the first registry visit, only 57 subjects (4.0%) were identified as having ssSSc. Of these, 30 (2.1%) were reclassified as lcSSc within 1.9 years. Thus, only 27 ssSSc subjects (1.9%) remained, with mean followup of 2.4 years. Clinical profiles of ssSSc were generally similar or milder compared to lcSSc, and milder than dcSSc, including rates of interstitial lung disease (25.9% ssSSc, 25.4% lcSSc, 40.3% dcSSc). Patients with ssSSc had serological profiles similar to those with lcSSc, including high rates of anticentromere antibodies (50.0% ssSSc, 47.5% lcSSc, 12.1% dcSSc), and low rates of antitopoisomerase I (16.7% ssSSc, 7.0% lcSSc, 21.8% dcSSc) and anti-RNA polymerase III (0 ssSSc, 11.1% lcSSc, 34.9% dcSSc). The condition ssSSc is rare and resembles lcSSc. These observations suggest that ssSSc is most likely a forme fruste of lcSSc, and that the absence of skin involvement may in part be related to misclassification arising from early or subtle skin involvement. There is little evidence to consider ssSSc as a distinct clinical or serological subset of SSc.